2017
DOI: 10.1021/acs.nanolett.7b04396
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Electrochemical Intercalation of Graphene/h-BN van der Waals Heterostructures

Abstract: Electrochemical intercalation is a powerful method for tuning the electronic properties of layered solids. In this work, we report an electrochemical strategy to controllably intercalate lithium ions into a series of van der Waals (vdW) heterostructures built by sandwiching graphene between hexagonal boron nitride (h-BN). We demonstrate that encapsulating graphene with h-BN eliminates parasitic surface side reactions while simultaneously creating a new hetero-interface that permits intercalation between the at… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 21 publications
6
53
0
Order By: Relevance
“…Recently, based on the same principle (intercalation/de-intercalation) as in electrochemical applications, guest species such as alkali metal ions (Li + , Na + , and K + ) have been introduced into the large interlayer spacing (~ 0.615 nm) to manipulate and optimize the optical and electrical properties of few-layer MoS 2 12 14 . Ion intercalation 12 , 15 24 enables extremely high doping level (e.g., 6 × 10 14 cm −2 in few layer graphene after Li intercalation 25 ) compared with electrical gating. Such high doping levels allow new physics to be discovered, such as superconductivity 26 and facilitates applications of few-layer MoS 2 in optoelectronic and nanoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, based on the same principle (intercalation/de-intercalation) as in electrochemical applications, guest species such as alkali metal ions (Li + , Na + , and K + ) have been introduced into the large interlayer spacing (~ 0.615 nm) to manipulate and optimize the optical and electrical properties of few-layer MoS 2 12 14 . Ion intercalation 12 , 15 24 enables extremely high doping level (e.g., 6 × 10 14 cm −2 in few layer graphene after Li intercalation 25 ) compared with electrical gating. Such high doping levels allow new physics to be discovered, such as superconductivity 26 and facilitates applications of few-layer MoS 2 in optoelectronic and nanoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Intercalation is the process of inserting various guest species into various vdW gaps formed at the interlayer interfaces [20,21] and vdWH interfaces. [22,23] In particular, for various future applications using vdW layered materials, Li-ion intercalation has received significant attention as one of the most attractive techniques for tuning electrical and optical characteristics, such as phase transition, [24][25][26][27] superconductivity, [28,29] ferromagnetism, [30] tunable thermal conductivity, [31] or tunable optical transmittance. [32,33] Our study demonstrated that Li ions intercalated to vdW interfaces lower the potential energy and Schottky barriers owing to the low potential energy of Li and the mild electron doping from intercalation, which can reduce the resistance at vdW interfaces and improve current flow for high-speed and lowpower n-type WSe 2 FETs.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the other approaches, however, electrochemical intercalation requires a more complex experimental set-up. 18,37,38 Therefore, strategies for the straightforward, reversible and gradual fine-tuning of nanosheet properties with soft chemical intercalation methods are in high demand.…”
mentioning
confidence: 99%